Generative AI in academic writing: Student reflections on using ChatGPT for thesis proposal development - La Sunra; Andi Muhammad Irawan; Andi Asrifan; Sivaraja Sadhasivam (Studies in English Language and Education, 2026)
The swift rise of generative artificial intelligence (AI) has revolutionized academic writing methods, with systems like ChatGPT becoming widely incorporated into higher education settings. Although current research has explored AI-assisted writing in essays and other general academic assignments, there has been no focus on its role in thesis proposal preparation, a genre that requires both linguistic precision and methodological clarity. This study examines postgraduate students’ reflections on their use of ChatGPT for drafting thesis proposals at one of the universities in Indonesia. Employing a qualitative case study approach, data were gathered through semi-structured interviews and document analysis involving eight students who utilized ChatGPT in their writing process. The results indicate that ChatGPT enhanced efficiency by decreasing drafting time, facilitated idea formation through varied views, and fostered creativity and vocabulary development. Students demonstrated adaptive prompting strategies and ethical awareness by verifying AI outputs. Through the lens of reflective practice in analyzing the data, the students’ reflections illustrated varying levels—from descriptive to critical—of engagement with AI as a cognitive and ethical collaborator in writing thesis proposals. The study concludes that structured reflection enhances students’ metacognitive regulation and ethical literacy in AI-assisted thesis writing. These findings contribute to the growing discourse on responsible AI integration in postgraduate academic writing contexts. Additionally, the study offers pedagogical implications for supervisors and institutions in guiding reflective and ethical use of generative AI tools.